Glaucomatous Progression After Lens Extraction in Primary Angle Closure Disease Spectrum. Issue 8 (August 2020) - Song, Min Kyung; Sung, Kyung Rim; Shin, Joong Won; Jo, Youn Hye; Won, Hun Jae
Abstract : Precis: Substantial proportion of primary angle closure glaucoma (PACG) eyes showed glaucomatous worsening after successful lens extraction and intraocular pressure (IOP) control, which may suggest that an earlier intervention may be required to prevent PACG. Purpose: The purpose of this study was to investigate the longitudinal clinical course of the primary angle closure (PAC) disease spectrum, including PAC, primary angle closure suspect (PACS), and PACG patients, who underwent lens extraction. Methods: This retrospective observational study included 77 eyes from patients with PACS, PAC, and PACG who underwent lens extraction and were followed up for >2 years after surgery. The mean, peak, and fluctuation of IOP were analyzed before and after lens extraction among groups. Visual field (VF) mean deviation was compared immediately after lens extraction and the final follow-up. Postoperative glaucoma progression determined by 3 criteria (optic disc/retinal nerve fiber layer photographs, optical coherent tomography, and VF) was compared among the 3 groups. Results: Seventeen PACS, 24 PAC, and 36 PACG eyes were included. The mean and peak IOP, and IOP fluctuation IOP were significantly reduced postoperatively in all groups. Postoperative VF mean deviation was significantly aggravated only in the PACG group (from −7.26 to −8.82 dB, P <0.001). The prevalence of postoperative glaucoma progression by at least 1 criterion was significantly higher in PACG, and none of the eyes with PACS and PAC showed VF conversion (PACS, PAC, PACG; 11.8%, 12.5% vs. 61.1% in disc/retinal nerve fiber layer, 11.8%, 8.3% vs. 63.9% in optical coherent tomography, 0%, 0% vs. 33.3% in VF, all P <0.001). Conclusions: In the PAC spectrum, lens extraction achieved significant IOP reduction. However, despite IOP control, a substantial proportion of PACG eyes showed glaucomatous progression. This result may suggest that lens extraction should be performed early to prevent PACG.